Impact of Physical Activities in Managing Stress Among CEOs in the Manufacturing Sector at Sri City Industrial Park - Janakiraman, Saravanan (Digital Repository of Theses, 2025)
This research is being conducted to explore and understand the problems of CEOs in managing stress and the effect of certain physical activity in coping up the stress to improve their quality of life. This study on stress management among CEOs in manufacturing industries helps the CEOS in identifying the factors which cause work stress and the effect of stress on them in the workplace. The study also emphasizes the ways the CEOs deal with stress and recommend best practices to effectively manage stress. The central question posed is what to cope with mechanisms and strategies CEOs perform in manufacturing industries to manage stress. This study is done using descriptive research design methods and data collected by primary and secondary sources. The questionnaire method is used as the methodology to collect primary data for the study with CEOs of manufacturing industries at Sri City Industrial Park. The survey had been conducted through an online questionnaire to collect the data. The findings of an Anova analysis done to look at and compare the variations in physical activity and the impacts of stress are shown in the forthcoming chapters. Analysing and contrasting variance resources can aid in determining which changes are important. This is the purpose of ANOVA. Since the value is greater than the significance threshold, the data demonstrates that there are no significant deviations. The respondents' level of physical activity has not changed in response to their level of stress. It is concluded that based on the input given through the survey responses and the statistical analysis the result is not in favour of any respondents, despite continuous attempt to practice any physical activity to reduce their stress level, except the Vigorous intensive physical activity. This study and analysis report depicts that the Top Management Employees across the Sri City Industrial Park are experiencing a tough situation in managing their operations with elevated level of stress to turn around the company for achieving their goal and profitability. It is imperative to have a workload sharing mechanism for such CEOs, who are lonely responsible for the Sales, Profit, Customer satisfaction, Operations Management, Staff Welfare, Statutory compliance, and Overall crisis management during the working tenure.